2017
DOI: 10.5306/wjco.v8.i5.412
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic lateral pelvic lymph node dissection in stage IV low rectal cancer

Abstract: AIMTo assess the clinical significance of prophylactic lateral pelvic lymph node dissection (LPLND) in stage IV low rectal cancer.METHODSWe selected 71 consecutive stage IV low rectal cancer patients who underwent primary tumor resection, and enrolled 50 of these 71 patients without clinical LPLN metastasis. The patients had distant metastasis such as liver, lung, peritoneum, and paraaortic LN. Clinical LPLN metastasis was defined as LN with a maximum diameter of 10 mm or more on preoperative pelvic computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Kanemitsu et al reported that, according to the index of the estimated benefits derived from LLND, dissection of the internal iliac and obturator nodes yielded similar therapeutic benefits as those expected from the dissection of the superior rectal artery lymph nodes [ 15 ]. Furthermore, Tamura et al reported no oncological benefit from performing LLND in patients with stage IV disease who had both lateral and distant lymph node metastases [ 33 ]. Oh et al reported that 59.1% of their patients with lateral lymph node metastases who underwent LLND also had distant metastases and poor prognoses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kanemitsu et al reported that, according to the index of the estimated benefits derived from LLND, dissection of the internal iliac and obturator nodes yielded similar therapeutic benefits as those expected from the dissection of the superior rectal artery lymph nodes [ 15 ]. Furthermore, Tamura et al reported no oncological benefit from performing LLND in patients with stage IV disease who had both lateral and distant lymph node metastases [ 33 ]. Oh et al reported that 59.1% of their patients with lateral lymph node metastases who underwent LLND also had distant metastases and poor prognoses [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen studies [ 7 , 17 , 42 , 45 , 46 , 48 , 49 , 52 , 53 , 57 61 , 64 , 66 , 68 , 69 ] reported local recurrence in 6613 patients (2.924 LLND and 3689 NLLND). The incidence of local recurrence was not statistically different between the overall LLND group (10.7%, 312/2.924) and the overall NLLND group (12.1%, 448/3.689) (RR 0.89, 95% CI 0.69 to 1.14; I 2 = 49%, P =0.36) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies [ 41 , 45 , 46 , 52 , 53 , 55 , 58 60 , 64 , 69 ], including 5132 patients (2560 LLND and 2572 NLLND), reported the rate of this outcome. The overall survival at 5 years was not statistically different between the LLND group (76.6%) and the NLLND group (74.6%), (RR 0.90, 95% CI 0.79 to 1.01; I 2 = 17%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the study Tamura et al study, all patients received R0 resection of primary site with the operative procedure as follows: 31 patients received low anterior resection, 18 patients received abdominoperineal resection, 1 patient received pelvic exenteration. 17 In this study, all patients received R0 resection of primary site with the operative procedure as follows: 15 patients received low anterior resection, 2 patients received abdominoperineal resection, 2 patients received ultralow anterior resection, 1 patient receive Intersphincteric resection.…”
Section: Discussionmentioning
confidence: 99%